Pollyanna [videorecording (DVD)] - Swift, David, 1919-2001; Swift, David, 1919-2001; Swift, David, 1919-2001; Mills, Hayley; Mills, Hayley; Wyman, Jane, 1917-2007; Egan, Richard, 1921-1987; Malden, Karl; Olson, Nancy, 1928-; Menjou, Adolphe, 1890-1963; Crisp, Donald, 1880-1974; Porter, Eleanor H. (Eleanor Hodgman), 1868-1920 (Distributed by Buena Vista Home Entertainment, 2002)
A young orphan brings sunshine into the lives of everyone she meets with her optimistic outlook on life.